1012. Efficacy, safety and tolerability of switching to bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in HIV-1 infected virologically-suppressed older adults in a real-world setting. (31st December 2020) - Rolle, Charlotte-Paige M; Nguyen, Vu; Patel, Kiran; Cruz, Dan; Hinestrosa, Federico; DeJesus, Edwin
Abstract: Background: Approximately 50% of people living with HIV (PLWH) in the United States are ≥50 years old. Efforts are ongoing to identify antiretrovirals associated with fewer drug-drug interactions (DDIs) and long-term side effects in this group. Clinical trials of B/F/TAF demonstrated favorable efficacy and safety in older adults, however, data from real-word settings are needed to validate these results. Methods: This retrospective analysis evaluated records from PLWH aged ≥ 50 years at the Orlando Immunology Center who were switched to B/F/TAF between 2/7/2018 and 5/31/2019. Eligible patients had baseline HIV-1 RNA< 50 copies/mL and were followed for 48 weeks post-switch. The primary endpoint was maintenance of HIV-1 RNA< 50 copies/mL at week 48. The impact of switching to B/F/TAF on DDIs, adverse events (AEs) and safety parameters were analyzed throughout the study. Results: 306 patients met inclusion criteria. 62 (20%) were female, 126 (41%) were non-white, median age was 58 years (range [r] 50-81), median duration of HIV infection was 19.5 years (r 2-40), median number of chronic co-morbid conditions was 5 (r 0-20), and median number of baseline concomitant medications was 4 (r 0-23). 159 (52%) patients were switched from regimens containing ritonavir or cobicistat. The most commonly documented reason for switch was simplification (Table 1). At Week 48, 287 (94%) patients maintained an HIV-1 RNA< 50 copies/ml and 19 (6%) had an HIV-1 RNA between 50-200 copies/mL (Figure 1). 1 patient discontinued due to lack of efficacy. A total of 123 potential DDIs were identified in 104 (34%) patients taking a boosting agent or rilpivirine at baseline (Table 2). At Week 48, there was a significant median decline in total cholesterol (15.5 mg/dL, 95% confidence interval [CI]: 9.5; 21.5), LDL cholesterol (9.5 mg/dL, 95% CI: 4; 15.5) and triglycerides (20 mg/dL, 95% CI: 9.5; 32.5), and median weight increased by 2.5 pounds (95% CI: 1.5; 3.5). Treatment-related AEs occurred in 33 (11%) patients (all Grade 1-2) and led to 7 (2%) discontinuations. Table 1-Baseline demographic and clinical characteristics Table 2-Avoidance of Drug-Drug Interactions (DDIs) following switch to B/F/TAF Figure 1-Subgroup analysis of virologic outcomes at Week 48 Conclusion: In this real-world cohort, switching to B/F/TAF was associated with maintenance of virologic control, improvement in lipid parameters, and avoidance of DDIs in a large proportion of patients. These data support use of B/F/TAF as a treatment option in older PLWH. Disclosures: Charlotte-Paige M. Rolle, MD MPH, Gilead Sciences (Grant/Research Support, Scientific Research Study Investigator, Speaker's Bureau)Janssen Infectious Disease (Grant/Research Support)ViiV Healthcare (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau) Kiran Patel, PharmD, Gilead Sciences (Employee) Federico Hinestrosa, MD, AbbVie (Speaker's Bureau)Gilead Sciences (Speaker's Bureau)Merck (Speaker's Bureau)Theratechnologies (Speaker's Bureau) Edwin DeJesus, MD, Gilead Sciences (Advisor or Review Panel member)